2018
DOI: 10.1177/1059840518760983
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization Type and Feeling Unsafe in Middle School

Abstract: Given their significance to school violence, this study quantifies the association between bullying victimization and perceptions of safety separately for victimization where the type is not specified versus victimization that is physical in nature. Generalized liner mixed modeling was employed with 5,138 sixth- to eighth-grade students in 24 schools who self-reported on their bullying victimization and perceptions of school safety on an anonymous survey in fall 2015. Results indicate a multiplicative interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…Previous research has likewise shown that bullying victimization was associated with staying home from school due to feeling unsafe (Williams, Schneider, Wornell, & Langhinrichsen-Rohling, 2018). Among middle school children ( N = 5,138), bullying victimization has also been associated with feeling unsafe at school (OR = 3.1); physical bullying (OR = 9.12) has especially been associated with weapon carrying (Bowser, Larson, Bellmore, Olson, & Resnik, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has likewise shown that bullying victimization was associated with staying home from school due to feeling unsafe (Williams, Schneider, Wornell, & Langhinrichsen-Rohling, 2018). Among middle school children ( N = 5,138), bullying victimization has also been associated with feeling unsafe at school (OR = 3.1); physical bullying (OR = 9.12) has especially been associated with weapon carrying (Bowser, Larson, Bellmore, Olson, & Resnik, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to bullying at school is common among adolescents [1][2][3] and associated with a range of health problems [2,4], risk behaviours [5], suicidal ideation [6], and negative school experiences [7][8]. Qualitative studies show that students exposed to bullying reported a wide range of negative emotional experiences: sadness, decreased self-esteem, embarrassment, fear, suicidal thinking, anger, feeling hurt, loneliness, powerlessness, helplessness, and confusion [9].…”
Section: Introductionmentioning
confidence: 99%
“…The findings obtained from the present research are in agreement with literature findings. Recent studies show that 20%–35% of adolescents are either victims, victimized, or both (Browser et al, 2018; Calpbinici & Tas Arslan, 2019). Studies on internet addiction show that 2.47%–7.02% (Kılıç et al, 2016; Pan et al, 2020) and 17.4% (Lin et al, 2018) of children and youth, respectively, are at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The findings obtained from the present research are in agreement with literature findings. Recent studies show that 20%-35% of adolescents are either victims, victimized, or both (Browser et al, 2018;Calpbinici & Tas Arslan, 2019).…”
Section: Discussionmentioning
confidence: 99%